Metaparadigm Menjawab Metaphor Teori Organisasi sebagai Pendulum dan Puzzle Solving - Tiara Puspa, Tiara Puspa (Benefit, 2007)
From growth of history, organization theory could be metaphoraly as apendulum which one time resided in right side and an other time resided in theother , meanwhile from the empiric study many debate around in analyzerswhich one better be applied, from this side organizational theory could also bemetahporaly like puzzle game. To overcome the motion of pendulum and finishpuzel in organizational theory hence discussion from all the viewpoints tried topulled to the above of into higher level that is multi paradigm. Approach ofmuliparadigm appreciate the possibility existence of equation in opinion issomething not possibly and there is existence of equation opinion in difference.Approach of multiparadigm give implication the importance of studyinterdisipliner in research of organization for getting more fully theory building.